Methods of treatment of pleural empyema in children - Barglik, Roksana; Korlacki, Wojciech; Grabowski, Andrzej (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Pleural empyema is caused by the accumulation of purulent content in the pleural cavity. In recent years, a higher incidence of pleural empyema in children has been observed. Pleural empyema is usually caused by the passage of infection from inflamed pulmonary tissue. The appropriate medical imaging and laboratory tests, including microbiological examination of the pleural cavity contents, enable the initiation of proper methods of treatment. Depending on the clinical condition of the patient, variable methods of treatment are used, such as: antibiotic therapy with simultaneous systemic therapy, thoracentesis, pleural cavity drainage with optional intrapleural fibrinolysis, thoracoscopic debridement of the accumulated effusion and fibrin accumulation, as well as lung decortication via open surgery or by thoracoscopic technique.